2007
DOI: 10.1038/emm.2007.84
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of HIV-1 Tat-induced monocyte adhesiveness by a cell-permeable superoxide dismutase in astrocytes

Abstract: HIV-1 Tat is considered to be one of key players to facilitate monocyte entry into the CNS, which is characteristic feature of AIDS-related encephalitis and dementia. This study was performed to determine the regulatory function of superoxide dismutase (SOD) on the HIV-1 Tat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The MAPKs such as p38, JNK and ERK protein kinase are the principal components in the signaling cascades leading to activation of NF-κB upon various stimuli. Previous studies have shown that extracellular HIV-1 Tat can regulate the activity of MAPKs in astrocytes (Kutsch et al, 2000;Song et al, 2007a). MAPK inhibitors suppressed Tat-induced mRNA and protein expression of MMP-9 as well as gelatinolytic activity of MMP-9 ( Figure 3B).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The MAPKs such as p38, JNK and ERK protein kinase are the principal components in the signaling cascades leading to activation of NF-κB upon various stimuli. Previous studies have shown that extracellular HIV-1 Tat can regulate the activity of MAPKs in astrocytes (Kutsch et al, 2000;Song et al, 2007a). MAPK inhibitors suppressed Tat-induced mRNA and protein expression of MMP-9 as well as gelatinolytic activity of MMP-9 ( Figure 3B).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have indicated that extracellular HIV-1 Tat has a regulatory effect on the activity of MAPKs such as p38, JNK and ERK protein kinase in astrocytes (Kutsch et al, 2000, Song et al, 2007a. To examine HIV-1 Tat-induced MAPK activation, CRT-MG cells were exposed to HIV-1 Tat (500 ng/ml) for various times, and then MAPK activation was analyzed by Western blot analysis using phospho-specific antibodies against MAPK proteins.…”
Section: Hiv-1 Tat Induced Mapk Activation Which Is Required For Mmp-mentioning
confidence: 99%
“…Another aspect of low Cu/Zn SOD function is altered monocyte chemotaxis. Cu/Zn SOD controls up-regulation of adhesion proteins by HIV-1 Tat-mediated reactive oxygen species (ROS) release in monocytes (Song et al, 2007). Moreover, unrestricted ROS production may facilitate NF-κβ induction, subsequent HIV long terminal repeat transactivation, and chronic viral replication upon cell maturation into macrophages (Israel and Gougerot-Pocidalo, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…RAW 264.7 cells were treated with LPS (100 ng/ml) for 30 min, then nuclear extracts of cells were prepared and analyzed for NF-κB binding activity, as described previously (Song et al, 2007). Five micrograms of nuclear extracts were equilibrated for 15 min in binding buffer (10 mM Tris-HCl, pH 8.0, 75 mM KCl, 2.5 mM MgCl2, 0.1 mM EDTA, 10% glycerol, 0.25 mM DTT) and 1 μg of poly dI/dC.…”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 99%